"Profits before people"? A systematic review of the health and safety impacts of privatising public utilities and industries in developed countries. Issue 10 (14th September 2007) - Egan, Matt; Petticrew, Mark; Ogilvie, David; Hamilton, Val; Drever, Frances
Abstract : Debates on government privatisation policies have often focused on the alleged effects of privatisation on health and safety. A systematic review (through Quality of Reporting of Meta-analysis) of the effects of privatising industries and utilities on the health (including injuries) of employees and the public was conducted. The data sources were electronic databases (medical, social science and economic), bibliographies and expert contacts. Experimental and quasi-experimental studies were sought, dating from 1945, from any Organisation for Economic Cooperation and Development member country (in any language) that evaluated the health outcomes of such interventions. Eleven highly heterogeneous studies that evaluated the health impacts of privatisation of building, water, paper, cement, bus, rail, mining, electric and gas companies were identified. The most robust study found increases in the measures of stress-related ill health among employees after a privatisation intervention involving company downsizing. No robust evidence was found to link privatisation with increased injury rates for employees or customers. In conclusion, public debates on the health and safety implications of privatisation have a poor empirical base, which policy makers and researchers need to address. Some evidence suggests that adverse health outcomes could result from redundancies associated with privatisation.